Перекладознавчі студії Івана Франка - Власенко, В.В. (Культура народов Причерноморья, 2013)
Стаття присвячена багаторічний перекладацькій діяльності Івана Франка. Як видатний діяч української й світової культури він переклав на українську мову більше 200 авторів з 14 мов 35 національних культур. У статті розглядаються переклади Івана Франка з різних мов, зосереджена увага на перекладах з німецької мови, яку він добре знав з дитинства, а також переклади з польської мови й твори російських письменників. У висновках ідеться про значення перекладацької діяльності Івана Франка. Він наближав своїми перекладами світову літературу до культури рідного народу, сприяв розвитку українського художнього слова. Статья посвящена многолетней переводческой деятельности Ивана Франко. Как выдающийся деятель украинской и мировой культуры он перевел на украинский язык больше 200 авторов с 14 языков 35 национальных культур. В статье рассматриваются переводы И.Франко из разных языков, сосредоточенное внимание на переводах с немецкого языка, который он хорошо знал с детства, а также переводы с польского языка и произведения русских писателей. Отмечено значения переводческой деятельности Ивана Франко, который приближал своими переводами мировую литературу к культуре родного народа, оказывал содействие развитию украинского художественного слова. This article is devoted to many years of Ivan Franco’s translation activity. As a famous figure in the Ukrainian and the world culture he translated into Ukrainian language more than 200 authors from the14 languages 35 national cultures. The Franсo’s translations from other literatures are made the 9 volumes of the 50-volume edition of writer’s works (VI-XIII, XXV). What other countries did a whole generation of the writers, translators and scholars, in Ukraine he made one. Selecting the objects for the translation from the foreign literature in Franco, as usual, is expressed not only the informative purpose: the selection of sources for the translation and their interpretation is usually due to its ideological and aesthetic convictions. The article deals with the translation of Ivan Franco from the different languages. The attention is focused on the translation of the German language, which he knew from the childhood, as well as translations from Polish and works of Russian writers. This intelligence allows understanding the contribution of Ivan Franco in the development of the theoretical and practical foundations of the translation. He edited, reviewed, analyzed other people's translations and wrote the foreword to his and others translations, translating articles. In the conclusion talked about the importance of Ivan Franco’s translations. He approached his translations of the world literature to the culture of the native people, put high demands to the art of the literary translation, contributed to the development of the Ukrainian artistic word.